Neutrophil-lymphocyte and platelet-lymphocyte ratios as inflammation markers for bipolar disorder. Issue 3 (30th August 2015) - Kalelioglu, Tevfik; Akkus, Mustafa; Karamustafalioglu, Nesrin; Genc, Abdullah; Genc, Esra Sena; Cansiz, Alparslan; Emul, Murat
Abstract: In the present study we investigated the involvement of inflammatory cells and their ratios as inflammation markers in Bipolar Disorder. We have enrolled 61 manic, 55 euthymic patients and 54 control subjects to the study. Neutrophil-lymphocyte and platelet-lymphocyte ratios were found significantly higher in both manic and euthymic patients compared to control group. These findings suggest that the inflammatory cells have a role in the pathophysiology of bipolar disorder manic and even in euthymic state. Highlights: Neutrophil-Lymphocyte and Platelet-Lymphocyte Ratios may be useful Inflammation Markers for Bipolar Disorder. Neutrophil and Lymphocyte counts are increased in manic and euthymic states.